2016
DOI: 10.1016/j.aca.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-performance liquid chromatography – Tandem mass spectrometry urinary pterinomics workflow

Abstract: Pteridines have evoked considerable interest from the scientific community owing to their prominent roles in human health and disease. The availability of analytical methodologies suitable for comprehensive pteridine profiling, termed here as "pterinomics", has been limited by inconsistent sample preparation and the exclusion of lesser studied pteridine derivatives. In response, the present study describes a new pterinomics workflow using a high-performance liquid chromatography - tandem mass spectrometry (HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…These data are contradictory with the results reported by Van Daele and co-workers. 27 However, results similar to ours have been recently described by Burton et al, 28 who found negligible in-source oxidation of 7,8-dihydroxanthopterin to xanthopterin. a Fragmentor voltage: 100 V, capillary voltage: 4500 V, nebulizer pressure: 30 psi, temperature: 300 C.…”
Section: Stability Of the Pteridines In The Tomato Extractsupporting
confidence: 91%
See 1 more Smart Citation
“…These data are contradictory with the results reported by Van Daele and co-workers. 27 However, results similar to ours have been recently described by Burton et al, 28 who found negligible in-source oxidation of 7,8-dihydroxanthopterin to xanthopterin. a Fragmentor voltage: 100 V, capillary voltage: 4500 V, nebulizer pressure: 30 psi, temperature: 300 C.…”
Section: Stability Of the Pteridines In The Tomato Extractsupporting
confidence: 91%
“…27 In the above mentioned paper the authors report that dihydropterins are subjected to interconversion, on column, in source and auto oxidation, and they are degraded into non-pterin products during boiling. Later, Burton et al 28 established the pterinomic workow for 15 pteridin derivatives in urine using HPLC-MS/MS revealing that previous oxidative steps were inefficient. The elimination of the preoxidation step in the analysis of pteridinic derivatives was previously recommended by Cañada et al 29 It is remarkable that Burton et al showed that 7,8-dihydroxanpthopterin exhibited negligible in-source oxidation to xanthopterin.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, HPLC‐mass spectrometry provides a means to detect neopterin more accurately. This technique has been shown to be robust in measuring urinary neopterin [53] and will be pursued in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of BH 4 present in the sample is calculated by determining the difference in biopterin content between the two different oxidation procedures. Most protocols are based on HPLC coupled to fluorescence detection, but there are also newer protocols available combining the separation via HPLC with MS/MS [126,128]. Analysis of urinary sepiapterin content has been shown to be a useful non-invasive tool to identify patients suffering from SRD [103].…”
Section: Diagnostic Methodsmentioning
confidence: 99%